CORE STABILITY EXERCISES LEBIH MENINGKATKAN AKTIVITAS FUNGSIONAL PADA NYERI PUNGGUNG BAWAH MIOGENIK - Nur Susanti (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2015)
Myogenic low back pain `is located around low back area. It is caused by musculoscletal disorders  without  neurologic  disorders  from  twelve  thoracal  vertebrae  to  the  hip.  It  is  caused  by static  and  dynamic  factors  that  is  causing  pain.  Low  back  muscle  spasms  and  its  surroundings cause  imbalance  muscle  activities.  Therefore,  it  decreases  instability  of  abdominal  and  low  back muscles. Limitation of lumbar movement decreases functional activities. Physiotherapy is intended to  relief  the  pain  and  more  relaxation  for    hospitalized  patience.  Meanwhile,  core  stability exercisesareto  increase  functional  activities  by  moving  transversus  abdominis,  multifidus, diafragma,  and  pelvic  floor  muscles.  The  research  was  aimed  at  testing  core  stability  exercises forimproving  myogenic  functional activities. The  research was designed as a  quasi eksperimental by using pre-test andpost-test design with control group. The research was held at RSUD Bendan Pekalongan Physiotherapy  installation. The research subject covered 28 patients. Measurement of functional  activities  of  myogenic  low  back  pain  was  conducted  by  using    oswestry  disability questionnaire (ODQ) before and after exercises. It was divided into  two groups as the control and treatment group. Control and treatment group was three times a week.  The result of this research was the  increasing of  ODQ score of control group for  p<0.05, and p<0.05 for treatment group. It means  that  control  group  and  treatment  group  can  improve  functional  activities  of  myogeniclow back pain. Comparation test of data by using independent test is p<0.05, whether before and after exercise.  The  average  of  control  group  is  8.14%.  The  average  treatment  group  is  28.57%.  It  is meant  that  treatment  group  is  good  for  improving  functional  activities  than  control  group.  The research  conclusion  was  that    core  stability  exercises  training  improv  the  functional  activities  in basic  therapy  of  myogeniclow  back  pain.  It  is  expected  that  core  stability  exercises  and  basic therapy can be used in patient with myogeniklow back pain to improve of functional activity.